A socio-economic assessment on the selected borrowers of micro financial institutions in Tacloban City. - Basog, Lenny Jane (Tacloban City Lenny Jane Basog [and] Mark Louie Serrano, 2010)
The purpose of this study is to identify and determine the socio-economic impact of micro financial institutions to its borrowers in Tacloban City.
Micro financial institutions are basically built to provide financial assistance such as loans to the poor so that they could invest in small businesses that would in turn give them additional income. Through these institutions poverty cab be alleviated. However, proper management of borrowed money should be employed. In this study, it was assessed that socio-economic impact of these institutions would greatly depend on the borrowers themselves. The positive impact of micro financial institutions was seen on the borrowers who utilized the money in productive way. On the other hand, negative impact appeared on those who have mishandled the money.
Undergraduate thesis (B.A.S.S. Economics)--University of the Philippines, Tacloban
Keywords: Social Science